Kecenderungan Kecurangan (Fraud) yang Dipersepsikan Melalui Keadilan Organisasi dan Peran Sistem Pengendalian Intern - Amelia Herman, Lisa; Ramadhea Jr, Syafira (Akuntansi dan Manajemen, 2021)
Public trust is the main capital of the banking business in carrying out its function of collecting and distributing public funds. Bank management must make efforts to maintain and maintain this trust in order to gain sympathy from prospective customers, such as obeying existing regulations and not making mistakes that cause irregularities and fraud. Fraud can be carried out by internal or external parties. One of the motivations for someone to commit fraud is a sense of justice. An individual who feels that he is being treated unfairly tends to act against the goals of the organization. In addition, the ineffectiveness of the internal control system allows opportunities to commit fraud that will have a negative impact on the company. This study aims to determine the effect of organizational justice and the role of the internal control system on fraud. Respondents as many as 164 employees of the main branch office of a government bank in the city of Padang were used as samples. The method that will be applied to analyze the data is multiple linear regression analysis with SPSS v.25 program. The results show that organizational justice and the role of the internal control system affect organizational fraud. This research can have implications for organizations to provide behavioral justice for each employee so that employee intentions to commit fraud can be avoided.